2006
DOI: 10.1037/0012-1649.42.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural influences on the development of verbal mediation: Private speech and phonological recoding in Saudi Arabian and British samples.

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 50 publications
3
62
1
1
Order By: Relevance
“…These findings are consistent with Vygotsky's (1930Vygotsky's ( -1935Vygotsky's ( /19781934/1987 ideas on the role of speech in cognition, and suggest planning can be considered to be largely verbally mediated in middle childhood. The results are consistent with the view that cognition undergoes a domain-general shift towards verbal mediation during early childhood (Al-Namlah et al, 2006;Fernyhough, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings are consistent with Vygotsky's (1930Vygotsky's ( -1935Vygotsky's ( /19781934/1987 ideas on the role of speech in cognition, and suggest planning can be considered to be largely verbally mediated in middle childhood. The results are consistent with the view that cognition undergoes a domain-general shift towards verbal mediation during early childhood (Al-Namlah et al, 2006;Fernyhough, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Experiment 2 showed that, when participants were forced to plan ahead, suppressing selfdirected speech was detrimental to Tower of London performance. The results of Experiment 2 support those of Fernyhough and Fradley (2005), Al-Namlah et al (2006), and Wallace et al (2009) in suggesting that planning is achieved with the aid of self-directed speech. These findings are consistent with Vygotsky's (1930Vygotsky's ( -1935Vygotsky's ( /19781934/1987 ideas on the role of speech in cognition, and suggest planning can be considered to be largely verbally mediated in middle childhood.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations